2005
DOI: 10.1021/om050844x
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Reactivities of New PCsp3P Pincer Complexes of Nickel

Abstract: Heating Ni(II) halides with 1 equiv of Bu t 2 P(CH 2 ) 5 PBu t 2 gives the PC sp3 P pincer complexes [{(Bu t 2 P-(CH 2 ) 2 ) 2 CH}NiX] (X ) Cl, 1a; Br, 1b; I, 1c). These compounds react with MeMgCl or n-BuLi to give, respectively, the methyl species {(Bu t 2 P(CH 2 ) 2 ) 2 CH}NiMe, 2, or the hydride species {(Bu t 2 P(CH 2 ) 2 ) 2 -CH}NiH, 3, while reaction with NaBPh 4 in a mixture of benzene/acetonitrile gives the cationic species [{(Bu t 2 P(CH 2 ) 2 ) 2 CH}Ni (NtCCH 3 )][BPh 4 ], 4. Complexes 1-3 are inert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 36 publications
6
52
0
Order By: Relevance
“…A similar zwitterionic by-product was observed by Zargarian and co-workers in their efforts to isolate Ni-pincer complexes incorporating tBu 2 P(CH 2 ) 5 PtBu 2 . 35 In this case, further protonation gave the salt [(tBu 2 PH(CH 2 ) 2 ) 2 CH 2 ]- [NiCl 4 ].…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…A similar zwitterionic by-product was observed by Zargarian and co-workers in their efforts to isolate Ni-pincer complexes incorporating tBu 2 P(CH 2 ) 5 PtBu 2 . 35 In this case, further protonation gave the salt [(tBu 2 PH(CH 2 ) 2 ) 2 CH 2 ]- [NiCl 4 ].…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…The crystal structure confirmed the distorted tetrahedral geometry of the N2CH carbon on the NCN pincer complex, with the sum of the bond angles formed by the heavier elements at C1 measuring 332.5º (Figure 1). With 1.848(5) Å, the C1-Ni1 bond is short when compared to similar bonds in nickel(II) pincer complexes featuring dialkylmethyl 16 or diarylmethyl 11 central platforms (av. Ni-C 1.98(2) and 1.986(3) Å, respectively).…”
mentioning
confidence: 99%
“…Oligomerization of PhSiH 3 and its addition to styrene. Our preliminary investigations of the reactivities of our PC sp3 P-Ni compounds showed that complexes ((tBu) 2 P(CH 2 ) 2 CH(CH 2 ) 2 P(t-Bu) 2 )NiX (X = Cl, Br, I, Me, H) [27] can catalyze the oligomerization of PhSiH 3 . For example, the reaction of excess PhSiH 3 (50-100 equivalents) with these complexes (ca.…”
Section: Catalytic Reactivities Of Pc Sp3 P-ni Complexesmentioning
confidence: 91%
“…Dry, oxygen-free solvents were employed throughout. The Ni and Pd organometallic complexes used in our studies as pre-catalysts have been prepared according to published procedures given in [15] (Ni complexes bearing amine-and olefin-functionalized Ind ligands), [20] (Ni-Ind complexes bearing SiMe 3 substituents), [21] (Pd-Ind complexes), and [27] (PC sp3 P-Ni complexes). PhSiH 3 was prepared from PhSiCl 3 and LiAlH 4 according to a published procedure [31].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation